The book of longings [large type] - Kidd, Sue Monk (2020)
"In her mesmerizing fourth work of fiction, Sue Monk Kidd takes an audacious approach to history and brings her acclaimed narrative gifts to imagine the story of a young woman named Ana. Raised in a wealthy family with ties to the ruler of Galilee, she is rebellious and ambitious, with a brilliant mind and a daring spirit. She engages in her furtive scholarly pursuits and writes narratives about neglected and silenced women. Ana is expected to marry an older widower, a prospect that horrifies her. An encounter with eighteen-year-old Jesus changes everything. Their marriage evolves with love and conflict, humor and pathos in Nazareth, where Ana makes a home with Jesus, his brothers, and their mother, Mary. Ana's pent-up longings intensify amid the turbulent resistance to Rome's occupation of Israel, partially led by her brother, Judas. She is sustained by her fearless aunt Yaltha, who harbors a compelling secret. When Ana commits a brazen act that puts her in peril, she flees to Alexandria, where startling revelations and greater dangers unfold, and she finds refuge in unexpected surroundings. Ana determines her fate during a stunning convergence of events considered among the most impactful in human history"--Web page.